Studi Literatur : Analisis Berpikir Komputasi Pada Guru dan Siswa Dalam Konteks Implementasi Kurikulum Merdeka - Avita Salsabila; Yahfizham Yahfizham (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Merdeka curriculum is a new curriculum from the Ministry of Education and Culture which is a renewal of the previous curriculum and educational changes to realize superior Indonesian Human Resources (HR) with the profile of Pancasila students. Computational thinking is a core skill needed and is considered by experts to be able to support the education sector in the 21st century, therefore computational thinking is part of the independent curriculum. For this reason, this research focuses on analyzing computational thinking in teachers and students in the context of implementing an Merdeka Curriculum. The purpose of this research is to find out, describe and to improve the analysis of computational thinking in teachers and students in the implementation of an Merdeka Curriculum. The method used in this research is the literature study method by identifying based on previous research in various literature sources to be analyzed. This research identified 5 previous journals published from 2022 to 2023. The result of this research is that the integration of computational thinking in the implementation of the Merdeka Curriculum has great potential and is an important step to improve the quality of learning or education in Indonesia in order to prepare or give birth to the next generation who are creative, innovative, able to solve problems and can be competitive in the digital era.